The Quest for Targets Executing MYC-Dependent Cell Transformation - Hartl, Markus (Frontiers in Oncology, 2016)
MYC represents a transcription factor with oncogenic potential converting multiple cellular signals into a broad transcriptional response, thereby controlling the expression of numerous protein-coding and non-coding RNAs important for cell proliferation, metabolism, differentiation, and apoptosis. Constitutive activation of MYC leads to neoplastic cell transformation, and deregulated MYC alleles are frequently observed in many human cancer cell types. Multiple approaches have been performed to isolate genes differentially expressed in cells containing aberrantly activated MYC proteins leading to the identification of thousands of putative targets. Functional analyses of genes differentially expressed in MYC-transformed cells had revealed that so far more than forty upregulated or downregulated MYC targets are actively involved in cell transformation or tumorigenesis. However, for determination which of the known, or yet unidentified targets are responsible for processing the oncogenic MYC program, further systematic and selective approaches are required. The search for critical targets in MYC-dependent tumor cells is exacerbated by the fact that during tumor development, cancer cells progressively evolve in a multistep process thereby acquiring their characteristic features in an additive manner. Functional expression cloning, combinatorial gene expression and appropriate in vivo tests could represent adequate tools for dissecting the complex scenario of MYC-specified cell transformation. In this context, the central goal is to identify a minimal set of targets that suffices to phenocopy oncogenic MYC. Recently developed genomic editing tools could be employed to confirm the requirement of crucial transformation-associated targets. Knowledge about essential MYC regulated genes is beneficial to expedite the development of specific inhibitors to interfere with growth and viability of human tumor cells in which MYC is aberrantly activated. Approaches based on the principle of synthetic lethality using MYC-overexpressing cancer cells and chemical or RNAi libraries have been employed to search for novel anticancer drugs, also leading to the identification of several druggable targets. Targeting oncogenic MYC effector genes instead of MYC may lead to compounds with higher specificities and less side effects. This class of drugs could also display a wider pharmaceutical window because physiological functions of MYC, which are important for normal cell growth, proliferation, and differentiation would be less impaired.